Upaya Mengatasi Kegagalan Comparator pada Module Gas Detector antara Sinyal Acuan dan Sinyal Masukan Sensor Jenis Catalytic Combution terhadap Pembacaan Indicator Value (%) - Ali Khamdilah; Eka Darmana (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
The purpose of this study is to determine the cause of failure in comparing the input signal sent by the sensor detector with the reference signal on the gas detector module. Against the background of the unreadable percentage of flammable hazardous gas leaks on the gas detector module. This study uses data collection methods by direct observation on the LPG SC ship Commander LVII, interviews with responsible ship crews, and literature studies. The data analysis used is descriptive quantitative. The conclusions obtained are: damage to the variable resistor (Zero adjust volume) as the root of the problem which will have an impact on the resulting reference signal will always change every time, and the need for replacement of spare parts on the variable resistor (Zero adjust volume), Comparison of the input values to the Integrated Circuit (IC) will determine the follow-up signal used to drive the % level indicator, the condition of the reference value must always be steady / steady in accordance with the desired set point with the aim that the detector sensor readings in detecting hazardous gas leaks can be measured properly.